Desempenho reprodutivo de diferentes genótipos de caprinos para a produção de carne submetidos a estação de acasalamento durante a época chuvosa no Estado do Ceará - Fernandes Filho, José Ivan Caetano (2007)
Aimed to evaluate the reproductive performance of cross bred and SPRD goats for meat production, mated during raining season in state of Ceará. It was performed on Vale do Curú Experimental Farm, sitted on Pentecostes using 24 cross bred goats ½ Anglo nubian x SPRD, 37cross breds ½ Boer x SPRD and 37 goats SPRD, with the breeding season happening in 2006, april and may, and lasting 42 days. The evaluated parameters were estrus frequency, birth rate, duration of pregnancy, prolificity, type of birth, weaning rate, mortality of kids, wheight of goats at beggining and ending of mating season and at birth, and gender and genotype efect over wheight at birth, at 40 days and weaning, that was performed at 90 days of age. The data were analized using q-quadratic test and means comparasion tests, under Tukey test at 5 % of probability. There were a increase of goats wheights during mating season. The genetic group ½ Boer x SPRD showed, by mean, estrus latter than others groups, but became similars on the rest of period. The kids deriving from cross with exotic breed bucks showed heavier than that deriving from SPRD bucks cross. Equally, male kids were heavier than female kids. On the others parameters there were an equivalency between groups. This way, the cross breds goats showed similars performances and were not better than SPRD goats, and the introduction of exotic gens for meat production improved the weight of kids from birth until weaning.